Edward Byrne Memorial Justice Grant, Nebraska Strategic Plan, 2012-2015 - Behm, Mike (2012)
The Consortium for Crime and Justice Research (CCJR) at the University of Nebraska at Omaha was tasked by the Nebraska Commission on Law Enforcement and Criminal Justice to facilitate the development of a three-year strategic plan for the use of Edward Byrne Memorial Justice Assistant Grant (JAG) funds. The Crime Commission serves as the State Administering Agency that is responsible for funding projects that fit into one or more of the seven JAG purpose areas: law enforcement programs; planning, evaluation, and technology improvement programs; prevention and education programs; drug treatment and enforcement programs; corrections and community corrections programs; prosecution and court programs; and crime victim and witness programs